2020
DOI: 10.1242/dmm.046441
|View full text |Cite
|
Sign up to set email alerts
|

Fibrodysplasia ossificans progressiva: current concepts from bench to bedside

Abstract: Heterotopic ossification (HO) is a disorder characterised by the formation of ectopic bone in soft tissue. Acquired HO typically occurs in response to trauma and is relatively common, yet its aetiology remains poorly understood. Genetic forms, by contrast, are very rare, but provide insights into the mechanisms of HO pathobiology. Fibrodysplasia ossificans progressiva (FOP) is the most debilitating form of HO. All patients reported to date carry heterozygous gain-of-function mutations in the gene encoding acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…Specifically, it has been shown that activin A, which is expressed by innate immune system cells, plays an important role in both promoting and resolving inflammation, particularly by blocking ACVR1 WT signaling. Activin A is effectively perceived as a BMP ligand by ACVR1 R206H leading to downstream BMP signaling via SMAD1/5/9(8), thus responding to activins A, AB, AC, and B, to which the wild-type ACVR1 is unresponsive [6]. The penetrance of the ACVR1/ALK2 gene mutations is complete, and they usually arise de novo [7].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, it has been shown that activin A, which is expressed by innate immune system cells, plays an important role in both promoting and resolving inflammation, particularly by blocking ACVR1 WT signaling. Activin A is effectively perceived as a BMP ligand by ACVR1 R206H leading to downstream BMP signaling via SMAD1/5/9(8), thus responding to activins A, AB, AC, and B, to which the wild-type ACVR1 is unresponsive [6]. The penetrance of the ACVR1/ALK2 gene mutations is complete, and they usually arise de novo [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the FOP phenotype is extremely consistent and easily recognizable when fully expressed, early diagnosis still presents a challenge to physicians. According to the registry of the International FOP Association (IFOPA), the mean age at which the first symptoms occur is 5.4 years, while the mean age of FOP diagnosis is 7.5 years [6]. Almost all patients with FOP are typically born with various types and degrees of congenital great toe malformations, such as bilateral hallux valgus malformation with the lack of a toe crease at the metatarsophalangeal joints, and, in some cases, macrodactyly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations